2021
DOI: 10.3390/analytica2040012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Interaction Liquid Chromatography Coupled with Fluorescence Detection (HILIC-FL) for the Quantitation of Octreotide in Injection Forms

Abstract: Octreotide is a synthetic cyclic octapeptide analogue of somatostatin-14. It is mainly administered for the treatment of acromegaly, severe diarrhea, and neuroendocrine neoplasias. In this work, a hydrophilic interaction liquid chromatography (HILIC) method with fluorescence (FL) detection was developed and validated for the quantitation of octreotide in solutions for injection. Chromatographic separation was performed on an XBridge®-HILIC analytical column under isocratic elution with a short chromatographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It has been reported that octreotide undergoes disulfide bond cleavage (ringopened form) upon treating with either HCl or NaOH. [12,24,25] This may lead to a significant decrease in the native fluorescence of octreotide. The suggested mechanism for octreotide hydrolysis with HCl and NaOH is shown in Figure 4.…”
Section: Effect Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that octreotide undergoes disulfide bond cleavage (ringopened form) upon treating with either HCl or NaOH. [12,24,25] This may lead to a significant decrease in the native fluorescence of octreotide. The suggested mechanism for octreotide hydrolysis with HCl and NaOH is shown in Figure 4.…”
Section: Effect Of Phmentioning
confidence: 99%
“…[4][5][6][7][8] There are not a large number of analytical methods for determining octreotide in its pure form and pharmaceutical formulation. These methods include high-performance liquid chromatography, [9][10][11] liquid chromatography, [12][13][14] electrophoresis, [15] proton ( 1 H) quantitative nuclear magnetic resonance, [16] spectrofluorimetry, [17] and voltammetry. [18] Generally, direct spectrofluorimetric methods based primarily on the measurement of the native drug fluorescence are of great interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ввиду гидрофильности не для всех соединений возможно подобрать оптимальные условия хроматографического разделения в обращенно-фазовом варианте ВЭЖХ. Альтернативой может стать применение жидкостной хроматографии гидрофильных взаимодействий [hydrophilic interaction liquid chromatography, HILIC] [21,22] либо дериватизация пептида с целью увеличения его липофильности [23]. Кроме того, за счет дериватизации может быть достигнута большая чувствительность при детектировании [23].…”
Section: Introductionunclassified